Assessment of the Elements and Oxides Concentration in the Dust of Asbestos Used in Roofs of Houses in Al-Qalluah Town, Yemen - Salem, Tahir Abdullah Abdulgabbar; Saeed, Adel Ahmed Mohammed (Journal of natural sciences, life and applied sciences, 2020)
In this research we evaluated elements and oxides concentration of corrugated asbestos cement used in the roofs of houses in Al-Qalluah area- Aden city, Yemen in the period from August to September 2018. In Aden city, many houses were built between 1880 and 1990 and therefore corrugated asbestos cement roofs as one type of asbestos boards, were used widely in coverage of the buildings and garages. Airborne asbestos fibers may remain suspended in the air for some time and can be carried long distances by wind before settling down. The risk of developing asbestos-related diseases, like lung cancer, is associated with the level and duration of exposure. All the dust samples collected from different sites in Al-Qalluah area were sent to the National Research Center- Cairo and analyzed by QUANTA FEG 250 polarized-light microscopy (PLM), using the EPA 600/R-93/116 method. The overall results of scanning PLM for dust samples have shown fibers of asbestos with diameter ranged between 2.634-22.49μm. PLM quantitative analysis coupled with EDAX TEAM have found the mean concentrations 39, 36.5, 19.2, 31.8, 36.7 and 28.4 wt/wt% with respect to C, O, Mg, Al, Si, and Ca, while the mean concentrations of oxides CO2, MgO, Al2O3, SiO2, CaO, SO3, Fe2O3, K2O and Cl2O, were 46.4, 13.6, 34.8, 47.5, 29.0, 29.1, 31.5, 32.0 and 43.8 wt/wt% respectively.Asbestos boards should be encapsulated by a safe material to prevent or reduce their risks and the authorities should stop asbestos impacts on the environment and human health.
Keywords: analysis of elements and oxides; asbestos cement corrugated; polarized-light microscopy; quantitative analysis; Elements and oxides analysis